The Characters’ Efforts to Save Face in Zhao Xin’s Short Story 剃脑袋 Tì Nǎodai (Skull Shave) - Adeline Sondang Octavia; Nurni Wahyu Wuryandari (Published by Confucius Institute UNS, 2025)
The short story Skull Shave (剃脑袋 Tì Nǎodai) by Zhao Xin (2012) narrates the experience of the character “I”, an eight-year-old boy named Er Xiao, who fears having his hair shaved. The story focuses on the interactions among three main characters: Er Xiao, his father, and Uncle Qingshui, the barber, which closely relate to the concept of face, self-image, shame, prestige, and social honor in Chinese culture. This research aims to explore how these three characters attempt to save face and how their efforts impact their interactions, reflecting the social and cultural values of Chinese society. Using both intrinsic and extrinsic approaches, the analysis focuses on the characters’ actions, dialogues, and attitudes in the story, as well as the cultural significance of face in Chinese sociocultural contexts. The findings indicate that the characters’ efforts to maintain face affect their relationships and convey a moral message on the importance of preserving harmony in social relations. The story also highlights Zhao Xin’s perceptiveness in capturing rural life, particularly through a child’s perspective. Through its simple narrative, the short story is able to elevate the social and cultural realities of Chinese society into a literary work.